NORMALITATEA ÎNTRE REALUL ȘI VIRTUALUL RELAȚIILOR SOCIALE POSTMODERNE ÎN RAPORT CU VOCAȚIA CREȘTINĂ - GOȚIA, Monica - Ștefana (Studia Universitatis Babeș-Bolyai Theologia Graeco-Catholica Varadiensis, 2024)
Normality between the Real and Virtual of Postmodern Social Relations in Relations to the Christian Vocation. The period of the last years, wich marked the world through the SarsCovid-19 virus pandemic, had a strong impact on the harmonious development of all those who transmuted the physical reality into the virtual one. Since isolation imposed for the purpose of the common good also had various negative effects, we can bring into question the normality between the real and the virtual of postmodern social relations in relation to the Christian vocation. In postmodern society, due to globalization, individual autonomy, the relativity of interpersonal relationships, and criticism of religion, moral life is eclipsed by economic primacy and the status it provides. Ethics does not appear as an unconditional ideal but as a response in liberal societies to fears related to the uncontrolled growth of economic, technological, scientific, media etc. powers of these, placing them in relation to the moral values of the Christian faith.